Optimum Number of Clusters in Randomly Distributed Wireless Sensor Networks - Singh Chandrawanshi, Veervrat; Kumar Tripathi, Rajiv; Pachauri, Rahul (International Journal of Engineering and Technology, 2018)
The wireless sensor networks (WSN) are energy constraint because of finite batteries used as energy resources. The efficient utilization of these energy resources and prolonging lifetime are the most crucial research challenges in WSN. Clustering is considered one of the best suitable technique that carries out efficient resource allocation and higher scalability for sensor networks. The clustered networks have a big concern on the optimum number of clusters in a network. In a WSN, such a number of clusters significantly contribute in the betterment of network life time, energy resource utilization, system scalability and efficient data routing. In the proposed work, an analytical approach has been explored that provides optimum number of cluster in a WSN for various topologies. The proposed method takes both free space and multipath losses into consideration by assuming that the base station is located at the boundary of the sensing field.Â